Penyeliaan klinikal sebagai moderator antara hubungan kemahiran klinikal dengan eksperimentasi latihan perubatan siswazah (housemanship) - Saleh, Nor Shela; Yaacob, Hashim Fauzy (Penerbit UTM Press, 2015)
This research was conducted in the Hospital Sultan Ismail, Johor. The study aimed to identify the level of second year trainee doctor in clinical skills of learning usages and experimentation learning achievements while in housemanship. Moreover, researchers will also identify whether the clinical supervision react as a moderator or non-moderator. The data collection showed the researchers have 125 number of questionnaire returned. Researchers have made a pilot study and receiving the alpha cronbach value of realibility is highest. Additional, researchers used the descriptive statistics (mean, frequency and percentage) and inferential statistics (pearson correlation and regression of hierarchical reporting) for data analyses. Findings showed the level of clinical skills used and the level of experimentation learning achievements is high. The correlation analyse showed there are positive correlation between the clinical skills used and the level of experimentation learning achievements. However, based on regression analysis of hierarchical reporting, the relationship is not influenced by a clinical supervision moderator. Based on the results achieved, first hypothesis is accepted but the second hypothesis was rejected.